MASSIVE INFESTATION BY GUSSEVIA UNDULATA (PLATYHELMINTHES: MONOGENEA: DACTYLOGYRIDAE) IN FINGERLINGS OF CICHLA MONOCULUS CULTURED IN THE PERUVIAN AMAZON - Mathews Delgado, Patrick (2012)
Cichla monoculus (Spix & Agassiz, 1831) is a species with great potential for breeding in controlled environments in the Peruvian Amazon. This fact that has led to semi-intensive and intensive production intended for human consumption. However, more studies are required regarding the population of parasites that are affecting breeding and development of the species. This study identified a high infestation of a monogenean species, Gussevia undulata (Kritsky, Thatcher, Boeger, 1986), in semi-intensively fish farming of C. monoculus. The prevalence was 100%, with mortality ofall fish. The mean intensity and mean abundance of the parasite was 168.5 of parasites per individual. This is the first report of high infestation by G. undulata in C. monoculus cultured from the Peruvian Amazon.